Anclando los significados, contribuyendo al diálogo: el uso de imágenes en la producción de relaciones y significados (2013)
What is it that images can do that cannot be done by words alone? This article illustrates and discusses how visual expressions act as helpers of dialogue – anchors of meaning. The main argument is that the inclusion of pictorial material is a useful way to develop poststructuralist thinking technologies to further expand our understandings of the complexities of communication in individual as well as collective sense-making. The primary aim of the article is to present the method –the image exercise 1– so as to inspire other researchers to explore its potential wit in their own research contexts. It will also be argued that the method presented has the potential of establishing bonding, political awareness and meaningful collective knowledge production among all participants involved in a research process.Keywords: relational methodologies, knowledge production, post structuralism, gender.